Ocular morphology and function in juvenile neuronal ceroid lipofuscinosis (CLN3) in the first decade of life. (4th May 2017) - Preising, Markus N.; Abura, Michaela; Jäger, Melanie; Wassill, Klaus-Heiko; Lorenz, Birgit
ABSTRACT: Purpose : CLN3 is a rare lysosomal storage disorder. The majority of the patients suffer from neurological degeneration in the first decade of life leading to death in the second or third decade. One of the first symptoms is a rapid visual decline from retinal degeneration. The aim of this study was to correlate the retinal changes in CLN3 as seen with spectral domain optical coherence tomography (SD-OCT) with functional data in patients in the first years after the subjective onset of ocular symptoms. Methods : Three unrelated children aged from 5.6 to 8.8 years, and with molecularly confirmed CLN3, underwent a comprehensive ophthalmological examination including visual acuity, fundus photography, fundus autofluorescence (FAF), electrophysiology (multifocal ERG), Goldmann visual fields, and SD-OCT. Results : A predominant loss of the first and second neuron retinal layers progressing from the macula to the periphery was identifed. The retinal nerve fibre layer (RNFL) displayed gliosis and an irregular lining of the inner limiting membrane. Compared to the preferential reduction of photoreceptor layer thickness in other maculopathies with pan-retinal involvement, the thickness of the first and second neuron layers was reduced simultaneously in CLN3. Functional testing by multifocal ERG reflected the degenerative progress. Semiquantitative evaluation revealed a generally reduced FAF. Conclusion : This is the first detailed morphological evaluation of CLN3 patients in the first years after the subjective onset of ocular symptoms. CLN3 is characterized by an early degeneration predominant of the first and second neuron compared to other macular and generalized retinal dystrophies. Imaging is instrumental for early diagnosis and gene-directed molecular analysis of this fatal disorder.